THE RELATIONSHIP BETWEEN SUSTAINABLE SUPPLY CHAIN AND BUSINESS PERFORMANCE: A META-ANALYSIS STUDY - Gunawan, Muhammad; Hadi, Suryadi; Kaseng, Saharuddin; Dwiwijaya, Kadek Agus (Jurnal Ekonomi dan Bisnis Airlangga, 2025)
Introduction: This study conducted a comprehensive meta-analysis to investigate the relationship between Sustainable Supply Chain Management (SSCM) and business performance. With increasing global environmental concerns, businesses are increasingly required to integrate sustainable practices into their supply chains. This study aims to address the inconsistencies of previous studies on SSCM and business performance. Methods: This study uses the Random Effect Size meta-analysis method through the Jamovi application to analyze empirical data from accredited journals. This study also identifies the publication bias of Meta-analysis. Results: The findings show that SSCM has a positive correlation with financial, environmental, and social performance. Overall, SSCM is associated with business performance. The study also identified moderator variables such as year of publication, country classification by income, country, industry type, and company size. The relationship is stronger in Developed countries, electronics, shipping, and MSME sectors. Conclusion and suggestion: SSCM has shown to have a significant positive correlation to financial, environmental, and social performance, with moderate social correlation. Future research needs to expand the sample, especially the social dimension, as published or unpublished studies may have different results.